2019
DOI: 10.1093/milmed/usy410
|View full text |Cite
|
Sign up to set email alerts
|

The Health Status of Veteran Employees Compared to Civilian Employees in Veterans Health Administration

Abstract: Introduction Veterans Health Administration (VHA) is undergoing changes in the practice of health care focusing on approaches that prioritize veteran well-being. Given transformation efforts, opportunities exist to enhance the health and well-being of patients and employees alike – a significant proportion of whom are veterans. To date, differences in health status between veteran and civilian employees within VHA have not been examined. Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…Follow-up frequency was not constant across all cohort participants. The study may also not be generalizable to nonveteran populations; US veterans have substantially greater financial and health burdens than the civilian population and are at an increased risk of disability, obesity, and other chronic conditions . Although most of the cohort was composed of non-Hispanic White men, it did also include a sizable number of women and participants of other races and ethnicities, which were included in our models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Follow-up frequency was not constant across all cohort participants. The study may also not be generalizable to nonveteran populations; US veterans have substantially greater financial and health burdens than the civilian population and are at an increased risk of disability, obesity, and other chronic conditions . Although most of the cohort was composed of non-Hispanic White men, it did also include a sizable number of women and participants of other races and ethnicities, which were included in our models.…”
Section: Discussionmentioning
confidence: 99%
“…The study may also not be generalizable to nonveteran populations; US veterans have substantially greater financial and health burdens than the civilian population and are at an increased risk of disability, obesity, and other chronic conditions. 29,30 Although most of the cohort was composed of non-Hispanic White men, it did also include a sizable number of women and participants of other races and ethnicities, which were included in our models. We were unable to account for participants' individual household income; however, a low-income or disability flag was used as a proxy for socioeconomic status, and we further adjusted for neighborhood-level socioeconomic factors.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Lastly, veterans themselves may have unique risk factors that would preclude generalizability to the rest of the non-veteran populations. There is evidence that those who utilize Veterans Affairs facilities for their care have different socioeconomic and medical problems than veterans who opt for community medical care; it would be reasonable to propose that there are differences between veterans and non-veterans as well [ 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, a large VA employee health study demonstrated similar rates of physical activity, diabetes, and hypertension between women veterans and civilians. However, women veterans reported more depression, PTSD, sleep disorders, and tobacco use . Henceforth, compared with nonveterans, women veterans likely represent a high-risk group .…”
Section: Discussionmentioning
confidence: 69%